PkM Kelompok SMK dalam Pemanfaatan Digital Art untuk Membentuk Manajemen Kewirausahaan di Simalungun - Anjar Wanto; Harly Okprana; Rizki Alfadillah Nasution (LPPM STIKOM Tunas Bangsa, 2022)
This PkM activity aims to improve skills and creativity and form partner entrepreneurship management (Students of SMK Swasta Anak Bangsa Simalungun Regency) so that later partners can make their products according to their respective wishes by utilizing digital art by marketing it using a marketplace. The PkM team provides training and assistance on entrepreneurship management to Partners in the hope that Partners can open their jobs without relying on and waiting for employment opportunities. This service is carried out at the Children of the Nation Private Vocational School in Simalungun Regency. The activity was carried out for two days, Monday and Tuesday, July 18 and 19, 2022, starting at 09.00-17.00 WIB, with 60 students as participants. This activity uses presentation/lecture methods, discussions, questions and answers, and practice/practice on making products such as digital keychain pins, digital screen printing t-shirts, digital wood screen printing and digital mug glass printing. The results of this service activity, based on the results of the Pre-test, showed that of the 60 students participating in PkM at this school, 34 students were able to answer questions >10 (57%) and <= ten as many as 26 students (43%) with an average score of 51. Meanwhile, based on the Post Test, students who were able to answer questions >10 were 57 students (95%) or an increase of 38% compared to before the PkM activity was carried out, and <= as many as three students (5%) with an average score of 71. So it can be concluded that students' knowledge about digital art increased after this PkM activity was carried out.